Dynamic System Model of the Role of Leadership Coaching on Employee Performance - Hartono, Budi; Darmawansyah, Muhamad Erman; Bedy Saskito, Dinda Iryawati (KEMAS: Jurnal Kesehatan Masyarakat, 2021)
Jakarta Cempaka Putih Islamic Hospital (RSI) experienced a decline in performance. Judging from the 2013 Bed Occupancy Rate (BOR) of 70.59%, it then dropped to 44.12% in 2016. Efforts to improve employee performance by coaching have been carried out, but not comprehensively in each Hospital unit. The study aims to look at the role of leadership coaching with a dynamic system model on employee performance at the Jakarta Cempaka Putih Hospital. Besides that, it is also to find out the role of inspirators, facilitators, motivators, as well as the pattern of system behavior characteristics between the role of leadership coaching on employee performance. Analytical research using quantitative methods with explanatory research design. The research sample was 86 taken by accidental sampling technique from the population of inpatient staff and medical support in May 2018. Data processing techniques were carried out in stages including univariate analysis, bivariate Chi-Square, multivariate logistic regression, and dynamic system models of causal loop diagrams formulated to the flow diagram. The instrument used in the form of a questionnaire. In general, the test results showed the influence of the role of leadership coaching on employee performance. Specifically, it shows the influence of the role of leadership coaching as an inspiration, facilitator, and motivator on employee performance. Then the pattern of system behavior characteristics for the next 10 years is in the form of exponential growth and in the next 20 years in the form of S-Shaped growth. Likewise, the behavior pattern of the coaching leadership system role for the next 10 years in the form of exponential growth. The leadership coaching role was found to have an effect on improving employee performance.